Edukasi Kesehatan Reproduksi bagi Wanita Premenopause dan Menopause di Masyarakat - Ulfah Agus Sukrillah; Siti Mulidah; Asrin Asrin; Munjiati Munjiati; Nastiti Nur Indriyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Menopause is a natural phase in a woman's life, marked by the permanent cessation of menstruation due to declining ovarian function. Many women experience menopause-related symptoms that impact their physical and psychological well-being. Lack of understanding about menopause often leads to unpreparedness in dealing with these changes. This community service program aims to enhance knowledge among premenopausal and menopausal women about reproductive health through education. The methods used include lectures, interactive discussions, and pre-test and post-test assessments to measure participants’ knowledge improvement. The results showed a significant increase in participants’ knowledge levels after the education program, with the “good” category increasing from 20% to 66.67%. Participants responded positively, stating that the provided information was highly beneficial for preparing for menopause. This program is expected to be sustainable with the involvement of healthcare workers and local communities to improve the readiness and quality of life of menopausal women